Electrochemical Efficiency of Tomato and Pineapple Peel Waste-Based Bio-Batteries with KCl Inclusion - Vivi Octhaviana; Yohandri Bow; Abu Hasan (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Biomass-based power sources have been developed in response to the growing global demand for sustainable energy. With an emphasis on improving performance by adding potassium chloride (KCl), this study investigates the possibility of employing leftover pineapple and tomato peels as bio-battery electrolytes. The study used an experimental approach in which liquid extracts from fruit waste were supplemented with different KCl concentrations and fermented for 11 days. Six pineapple-based and six tomato-based cells were stacked in Parallel to get the desired operating voltage. The findings showed that with a composition of 60:10 on the fifth day of fermentation, electrochemical performance was at its best. The hybrid design exceeded the original goal of 6 V and complied with SNI IEC 60086-1:2015 regulations by successfully achieving a peak total voltage of 7.8 V. The tomato-based system achieved a higher peak efficiency of 42%, whereas pineapple-based electrolytes exhibited higher ionic conductivity. Additionally, the KCl enrichment greatly enhanced charge transfer, leading to a maximum LED illumination durability of 720 minutes (12 hours). The hybrid pineapple-tomato bio-battery with KCl addition demonstrates significant potential as a sustainable, low-cost renewable energy solution, bridging the gap between waste valorization and practical low-power electronic applications. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 13: Climate Action